1998
DOI: 10.2165/00063030-199810040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Vaccines

Abstract: The development of vaccines against the herpesviruses has major public health importance because of the wide spectrum of associated clinical disease with this virus in both immunocompetent and immunocompromised populations. Because these viruses establish latent infections capable of subsequent reactivation, both immunotherapeutic and prophylactic vaccine strategies are needed. A range of vaccine formulations has been devised, largely as a result of the rapid growth in knowledge in molecular microbiology and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…IL-12-induced attenuation in Salmonella typhimurium higher doses could be overcome by lowering the dose of wild bacteria for immunization or by using plasmids expressing high concentrations of protein. Previous investigators suggested that an effective vaccine could be designed by plasmid DNA vaccine, prime-boost strategies and genetic alteration (Ganges et al, 2005;Jennings et al, 1998;Leroux-Roels and Leroux-Roels, 2009;Pena et al, 2008). Although rapid developments for new pathogens were limited by current vaccine technology, our results suggested that the vaccine technology using plasmid expressing IL-12 would be a rapid, easy method for new vaccine.…”
Section: Discussionmentioning
confidence: 61%
“…IL-12-induced attenuation in Salmonella typhimurium higher doses could be overcome by lowering the dose of wild bacteria for immunization or by using plasmids expressing high concentrations of protein. Previous investigators suggested that an effective vaccine could be designed by plasmid DNA vaccine, prime-boost strategies and genetic alteration (Ganges et al, 2005;Jennings et al, 1998;Leroux-Roels and Leroux-Roels, 2009;Pena et al, 2008). Although rapid developments for new pathogens were limited by current vaccine technology, our results suggested that the vaccine technology using plasmid expressing IL-12 would be a rapid, easy method for new vaccine.…”
Section: Discussionmentioning
confidence: 61%
“…Work on the development of such a subunit vaccine has focused on the viral envelope glycoprotein, designated gB (356). It seems likely that as more is learned about the immune system mechanisms involved in the control of the virus, it will become possible to induce immunologic protection with inactivated, recombinant DNA-produced vaccines (91,214). Although complete protection against CMV may not be achieved by vaccination, partial immunity may obviate the development of serious manifestations of CMV infection and disease.…”
Section: Active Immunizationmentioning
confidence: 99%
“…A range of vaccine formulations has been devised, largely as a result of the rapid growth in knowledge in molecular microbiology and genetic engineering, including live and inactivated whole virus vaccines and subunit vaccines consisting of recombinant viral glycoproteins in various adjuvants [ 72 ].…”
Section: Introductionmentioning
confidence: 99%